2022
DOI: 10.3390/insects13010068
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenomes of Nine Asian Skipper Genera and Their Phylogenetic Position (Lepidoptera: Hesperiidae: Pyrginae)

Abstract: In this study, complete mitochondrial genomes of nine species representing three tribes in the subfamily Pyrginae sensu lato were newly sequenced. The mitogenomes are closed double-stranded circular molecules, with the length ranging from 15,232 bp to 15,559 bp, which all encode 13 protein-coding genes (PCGs), two ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA) genes, and a control region. The orientation and gene order of these nine mitogenomes are identical to the inferred ancestral arrangement of insects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…The IGSs have also been found between different genes in the mitogenomes of other beetles, such as between trnW and trnC [8], nad2, and trnW [21], trnI and trnQ [4,22,23], and so on. Comparative analyses of IGSs suggest that the presence and location of the IGS may be useful for studying evolutionary history and species delimitation in insects [24,25], such as those in the families Meloidae [8,13], Cleridae [16], and Scarabaeoidae [18]. Although a recent study reported that the Dorcus velutinus complex had a large IGS (>50 bp) between trnS2 (UCN) and nad1 [20], very little is known about large IGSs in Prosopocoilus mitogenomes.…”
Section: Introductionmentioning
confidence: 99%
“…The IGSs have also been found between different genes in the mitogenomes of other beetles, such as between trnW and trnC [8], nad2, and trnW [21], trnI and trnQ [4,22,23], and so on. Comparative analyses of IGSs suggest that the presence and location of the IGS may be useful for studying evolutionary history and species delimitation in insects [24,25], such as those in the families Meloidae [8,13], Cleridae [16], and Scarabaeoidae [18]. Although a recent study reported that the Dorcus velutinus complex had a large IGS (>50 bp) between trnS2 (UCN) and nad1 [20], very little is known about large IGSs in Prosopocoilus mitogenomes.…”
Section: Introductionmentioning
confidence: 99%
“…Intergenic spacers (IGS) are non-coding regions that are found between genes and are typically found in Metazoa and most vertebrate animals and in most cases serve as a transcription promotor mitogenomes(Saton et al, 2016;Yang et al, 2018) and, they have in uence on the growth rate of some invertebrate animals(Gorokhova et al, 2002). They are important signal for evolutionary studies and even species delimitation(Xi et al, 2015;Xu et al, 2022;Xiao et al, 2022). Besides IGS event, there is also segments of gene overlapping in mitochondrial genome(Chandhini et al, 2021).…”
mentioning
confidence: 99%
“…Our annotation/re-annotation and new assembly of the mitogenomes of Erynnis tages, Erynnis popoviana and Erynnis brizo brizo revealed that they share S1NGO with E. montanus (Figure 8). The presence of S1NGO in the mitogenome of E. popoviana was unrecognized in the paper describing it [37]. However, the comparison of the trnN and trnS1 sequences, identified during reannotation, with the orthologous counterparts of other Erynnis species provides compelling evidence in favour of this genomic arrangement (Figure 8).…”
Section: Miqgomentioning
confidence: 99%
“…We also sequenced the mitogenomes of two endangered butterflies, Parnassius apollo and Lopinga achine. Finally, we assembled the mitogenomes of the skippers Erynnis brizo brizo, Gesta gesta and Ephyriades brunnea brunnea, starting from available Illumina reads [36], as these taxa are key species for better understanding the evolution of S1NGO within the Hesperiidae [37] (see below).…”
Section: Imqgo; Euripus Nyctelius; Species Of Ants Beatles and Aphidsmentioning
confidence: 99%
See 1 more Smart Citation